SISTEM MANAJEMEN STOK BARANG PADA TOKO SEMBAKO IBUK ISUM BERBASIS CLOUD - Muhammad Efendi; Khairil Azhar; Ferdiansyah; Novrizal Nur (Digital Business Insights Journal, 2025)
Efficient stock management is a primary need in running a grocery store, especially to avoid shortages or excess inventory. Mrs. Isum's Grocery Store located in Teluk Kiambang Village still uses a manual recording method that is prone to errors, data loss, and irregularity in stock monitoring. This study aims to design a more structured and easy-to-use stock management system to support the smooth operation of the store. This system is designed with a simple but effective approach, containing features for recording incoming and outgoing goods, current stock information, and monthly reports that can be accessed quickly. By implementing this system, shop owners can control stock more accurately and efficiently. The implementation results show an increase in data accuracy and ease in the decision-making process related to procurement of goods.